A new species of Xenylla Tullberg, 1869 (Collembola: Hypogastruridae) from Peru, with a key to Neotropical species of the genus - Sternalski, Jakub; Paśnik, Grzegorz (Zootaxa, 2019)
A new species belonging to genus Xenylla Tullberg, 1869 from Peru is described and illustrated. The new species, Xenylla gwiazdowiczi sp. nov., can be distinguished from previously described Xenylla species by combination of the following characters: mucro separated from dens, presence of complete row of setae c on dorsal side of the head, four thick sensilla on antennal segment IV, 19,19,18 setae on tibiotarsi of legs I–III, slightly serrated setae on abdominal segments V–VI, presence of two weakly clavate tenent hairs on each leg. The new species resembles X. spinosissima Najt & Rubio, 1978 and X. humicola (Fabricius, 1780). Similarities between them have been discussed. An identification key to Neotropical species of the genus is provided.